2009
DOI: 10.1016/j.trstmh.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

α1-acid glycoprotein and α1-antitrypsin as early markers of treatment response in patients receiving the intensive phase of tuberculosis therapy

Abstract: The identification of early markers that predict the response to anti-tuberculosis treatment would facilitate evaluation of new drugs and improve patient management. This study aimed to determine whether selected acute phase proteins and micronutrients measured at the time of diagnosis and during the first weeks of treatment could predict treatment responses during the 2-month standard intensive phase of therapy. For this purpose, alpha1-antitrypsin, alpha1-acid glycoprotein, alpha2-macroglobulin, C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…However, we know that a proportion of LTBI at some point reactivate and develop active disease, and this may be preceded by a “fight” between host and microorganism leading to inflammatory responses that could have long term impact on the infected person. The acute phase reactant alpha-1-acid glycoprotein (AGP) has previously been associated with active TB [7], [8] and it might be a marker of inflammation in regards to LTBI. The primary objective was to estimate the prevalence of LTBI in household contacts of pulmonary TB cases and a group of apparently healthy neighborhood controls in an urban setting in a TB high endemic country.…”
Section: Introductionmentioning
confidence: 99%
“…However, we know that a proportion of LTBI at some point reactivate and develop active disease, and this may be preceded by a “fight” between host and microorganism leading to inflammatory responses that could have long term impact on the infected person. The acute phase reactant alpha-1-acid glycoprotein (AGP) has previously been associated with active TB [7], [8] and it might be a marker of inflammation in regards to LTBI. The primary objective was to estimate the prevalence of LTBI in household contacts of pulmonary TB cases and a group of apparently healthy neighborhood controls in an urban setting in a TB high endemic country.…”
Section: Introductionmentioning
confidence: 99%
“…The literature also supports the idea that a slower decline in these biomarkers over the course of treatment correlates with poorer treatment response [18,41]. Many have reported in small studies that CRP, sIL-2Rα, sTNF-R1, sTNF-r2, and neopterin were higher at baseline or failed to decline as rapidly in slower treatment responders or treatment failures[8,9,12,17,18,28,41]. Here, we have replicated the findings of Siawaya and colleagues in observing a treatment-related decline in all analytes except granzyme B, but no difference in these analytes between fast and slow treatment responders (as defined by 8 week culture status) in univariate analyses.…”
Section: Resultsmentioning
confidence: 68%
“…Multiple studies have reported that levels of these markers either correlate with TB infection, disease extent and severity, or decline over the course of intensive therapy[7,10,13-15,24,27,39,40]. The literature also supports the idea that a slower decline in these biomarkers over the course of treatment correlates with poorer treatment response [18,41]. Many have reported in small studies that CRP, sIL-2Rα, sTNF-R1, sTNF-r2, and neopterin were higher at baseline or failed to decline as rapidly in slower treatment responders or treatment failures[8,9,12,17,18,28,41].…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies have identified blood transcriptional signatures that correlate with disease severity and reversion in response to treatment [45] or patients who relapse rather than achieve lasting cures [46]. Other studies [4749] have evaluated the serum host biomarkers reflecting treatment responses at earlier time points or in relation to sputum culture conversion. One important advantage of our findings, is that circulating BK and DABK levels represent the host's response to pathogen–associated molecular patterns and may offer a rational route forward in the prediction of real-time treatment outcomes at both early and late treatment stages and allow individualization of treatment regimens, dosing, and treatment duration.…”
Section: Discussionmentioning
confidence: 99%